THE INFLUENCE OF NOVOALTAYSK BREED OF HORSES IN THE DEVELOPMENT OF PRODUCTIVE HORSE BREEDING IN THE NORTH-EAST OF KAZAKHSTAN - ASSANBAYEV, T.; SHAMSHIDIN, A. S.; TEMIRZHANOVA, A.; IBRAEVA, A.; BEXEITOV, T.; USSENOVA, L.; AMANBAEVA, S.; Шамшидин, Ә. С. (AD ALTA: Journal of Interdisciplinary research, 2019)
Relatively high demand and the market price for horse meat ensure the profitability of a herd of horse breeding for meat, promote the financial interest of farmers in the development of the livestock industry.Относительно высокий спрос и рыночная цена на конину обеспечивают рентабельность стада коневодства по мясу, способствуют финансовой заинтересованности фермеров в развитии животноводства.
Keywords: коневодство; импакт-фактор 2019; конина; зарубежное издание; цена на конину; дальнее зарубежье; рыночная стоимость конины; томсон; научный журнал; периодическое издание